(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The purpose of the numerical analysis presented in this study was to evaluate the benefit of increase the spacing transvers stirrups across web of beams subjected to behaivour shear Where the variable in this study exceeded paragraph (9.9.4.3) stipulated by (ACI 318R-19) by increasing the transverse spacing across web